Selective deletion of PPARβ/δ in fibroblasts causes dermal fibrosis by attenuated LRG1 expression - Sng, Ming Keat (2018)
Connective tissue diseases of the skin are characterized by excessive collagen deposition in the skin and internal organs. Fibroblasts play a pivotal role in the clinical presentation of these conditions. Nuclear receptor peroxisome-proliferator activated receptors (PPARs) are therapeutic targets for dermal fibrosis, but the contribution of the different PPAR subtypes are poorly understood. Particularly, the role of fibroblast PPARβ/δ in dermal fibrosis has not been elucidated. Thus, we generated a mouse strain with selective deletion of PPARβ/δ in the fibroblast (FSPCre-Pparb/d−/−) and interrogated its epidermal and dermal transcriptome profiles. We uncovered a downregulated gene, leucine-rich alpha-2-glycoprotein-1 (Lrg1), of previously unknown function in skin development and architecture. Our findings suggest that the regulation of Lrg1 by PPARβ/δ in fibroblasts is an important signaling conduit integrating PPARβ/δ and TGFβ1-signaling networks in skin health and disease. Thus, the FSPCre-Pparb/d−/− mouse model could serve as a novel tool in the current gunnery of animal models to better understand dermal fibrosis.